PENGARUH EFEKTIVITAS PENGGUNAAN EDMODO TERHADAP KEPUASAN SISWA DI SMKN 1 SURABAYA - Sudarsi, Sudarsi (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2017)
This study aims to determine the effectiveness level of Edmodo use, to know the level of student's satisfaction in using Edmodo and the effect of Edmodo effectiveness on student's satisfaction in using Edmodo in SMK Negeri 1 Surabaya. The method used is the quantitative method. As the object of this study is students of SMK Negeri 1 Surabaya who asked his opinion about the effectiveness and satisfaction of students in using Edmodo. In this study took a sample of class X with the number of respondents as many as 277 students spread in 9 majors and 24 classes. Samples are taken evenly of each class at random. Data collection was done by questionnaire and data analyst method was done by simple linear regression. Conclusion analysis as follows: 1). Edmodo Efektitifas by Students SMK Negeri 1 Surabaya is in the high category, but some students have not felt the benefits of Edmodo in learning. 2). Student Satisfaction SMK Negeri 1 Surabaya in using Edmodo is in the high category, but some students are not satisfied with the content group and students are less satisfied with the backpack content. 3). There is a significant effect of Edmodo Effectiveness on students' satisfaction in using Edmodo in SMK Negeri 1 Surabaya.